2014
DOI: 10.1021/ol501809p
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Tandem Hydroamination/Hydroarylation of 1-(2-Allylamino)phenyl-4-hydroxy-but-2-yn-1-ones to 1′-Allylspiro[indene-1,2′-indolin]-3′-ones

Abstract: An efficient silver triflate-catalyzed tandem hydroamination/hydroarylation cascade generating 1'-allylspiro[indene-1,2'-indolin]-3'-ones from 1-(2-allylamino)phenyl-4-hydroxy-but-2-yn-1-ones is described. The reaction conditions are mild and general in scope and proceed to highly functionalized spiro-targets in high yield. This novel class of molecule possesses both the privileged indene and indolin-3-one scaffold, which may lead to possible pharmacological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Mechanistically, the reaction proceeded by the initial oxidative dearomatization of 2-alkynylanilines 211, followed by the silvercatalysed sequential heterocyclization, Michael-type addition with silyl enol ethers 212 to install the 4-acetonyl group onto the indole ring and the final tandem rearomatization/protodemetalation to reconstruct the indoles. 166 Under the catalysis of AgOTf (10 mol%), the efficient tandem hydroamination and hydroarylation of propargylic alcohols 218 occurred, resulting in highly functionalized spirocyclic products 219 in high yields (80-94%). Propargylic alcohols are readily available functionalized alkynes; 161 additionally, the close proximity of the hydroxyl group to the carbon-carbon triple bond in one molecular scaffold imparts these molecules with extraordinary potential to undergo reactions that are distinct from those of alkynes alone.…”
Section: Cyclizationmentioning
confidence: 99%
“…Mechanistically, the reaction proceeded by the initial oxidative dearomatization of 2-alkynylanilines 211, followed by the silvercatalysed sequential heterocyclization, Michael-type addition with silyl enol ethers 212 to install the 4-acetonyl group onto the indole ring and the final tandem rearomatization/protodemetalation to reconstruct the indoles. 166 Under the catalysis of AgOTf (10 mol%), the efficient tandem hydroamination and hydroarylation of propargylic alcohols 218 occurred, resulting in highly functionalized spirocyclic products 219 in high yields (80-94%). Propargylic alcohols are readily available functionalized alkynes; 161 additionally, the close proximity of the hydroxyl group to the carbon-carbon triple bond in one molecular scaffold imparts these molecules with extraordinary potential to undergo reactions that are distinct from those of alkynes alone.…”
Section: Cyclizationmentioning
confidence: 99%
“…Therefore, great efforts have been devoted to the construction of these structures. Current syntheses are mainly based on four strategies, i.e., the oxidative rearrangement of 2,3-disubstituted indoles [49][50][51][52][53], cyclization reactions from acyclic starting materials [54][55][56][57][58][59][60][61][62], direct transformation from corresponding 3H-indol-3-ones or indolin-3-ones [63][64][65][66][67][68][69][70][71], and oxidative dearomatization of indoles [72][73][74][75][76]. Direct C-H functionalization of indoles with different C-H nucleophiles presents an atom-economic protocol without prior installation of activating groups and is thus very attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that AgOTf-catalyzed dehydrative cycloisomerization proceeding through the tandem hydroamina-tion/hydroarylation steps of substituted 2-alkynonanilines 305 is an efficient method for constructing spirofused indene-indolinones 306 (Scheme 81). [292] A well-established approach to the synthesis of Nheterocycles using tandem annulation of diazo compounds with amino alkynes [293] was also distributed to obtain spiro derivatives of indole or other heterocycles. So, 2-ethynylanilines 307 react with Meldrum's acid diazo 308 in the presence of the rhodium catalyst to provide the desired product 309a or the benzyl protected compound 309b (Scheme 82).…”
Section: Synthesis Strategy For Spiro-fused Heterocycles From 2-alkynmentioning
confidence: 99%